Local Government Fiscal Sustainability: A Case study of Local Government in Chiang Mai Province, Thailand - Jaikampan, Kraiwuth (King Prajadhipok’s Institute Journal, 2021)
This research aims to analyze the fiscal sustainability of local governments in Chiang Mai Province, Thailand, between the fiscal year of 2012-2016 and propose guidelines for enhancing local government financial sustainability. The researcher utilizes a mixed-method sequential explanatory research design with data collected from 81 local governments located in the provincial area. The quantitative results depict that the means of cash solvency, budget solvency, and service-level solvency indices are low, whereas the mean of long-term solvency index is high. The qualitative results approach several guidelines for local fiscal sustainability contingent on four dimensions, including enhancing appropriate local authority, local economic development policy, local competency in structuring institutional policy and fiscal system operation, and administrative capacity for monitoring the fiscal condition. In short, this research illustrates the implementation of such indices, and then it utilizes the results to create suggestions for streamlining the fiscal sustainability of local governments in Thailand.